2015
DOI: 10.1038/srep18304
|View full text |Cite
|
Sign up to set email alerts
|

PERK regulated miR-424(322)-503 cluster fine-tunes activation of IRE1 and ATF6 during Unfolded Protein Response

Abstract: The endoplasmic reticulum (ER) responds to changes in intracellular homeostasis through activation of the unfolded protein response (UPR). UPR can facilitate the restoration of cellular homeostasis, via the concerted activation of three ER stress sensors, namely IRE1, PERK and ATF6. Global approaches in several cellular contexts have revealed that UPR regulates the expression of many miRNAs that play an important role in the regulation of life and death decisions during UPR. Here we show that expression of miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…Although the murine ortholog of miR-424, miR-322, is downregulated by activation of the UPR in mouse embryonic fibroblasts (Gupta et al, 2015), miR-424 is not constitutively expressed in the cells used in this study (Chamorro-Jorganes et al, 2011), nor did we detect the miRNA during DENV2 or WNV infection (data not shown). The absence of endogenous miR-424 expression allowed us to use the miR-424 mimic as a tool to identify cellular factors required for viral replication.…”
Section: Discussionmentioning
confidence: 72%
“…Although the murine ortholog of miR-424, miR-322, is downregulated by activation of the UPR in mouse embryonic fibroblasts (Gupta et al, 2015), miR-424 is not constitutively expressed in the cells used in this study (Chamorro-Jorganes et al, 2011), nor did we detect the miRNA during DENV2 or WNV infection (data not shown). The absence of endogenous miR-424 expression allowed us to use the miR-424 mimic as a tool to identify cellular factors required for viral replication.…”
Section: Discussionmentioning
confidence: 72%
“…Under continuous ERS, the UPR can be triggered as a prosurvival process through the transient termination of translation, the induction of a large number of proteins that coordinately function to renature unfolded proteins. However, under conditions of persistent ERS, proapoptotic signals are induced through the activation of several transcription factors, such as CHOP, which is a key downstream regulatory factor of ERS pathway . The data demonstrated that MgIG at 5 mg/mL upregulated the expression of both Calnexin and CHOP in HSCs effectively (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…MicroRNAs (miRNAs) have emerged recently as key players in UPR signaling in mammalian cells (Maurel and Chevet, 2013), where there is evidence for their involvement in regulating gene expression during ER stress responses (Bartoszewska et al, 2013;Byrd and Brewer, 2013;Gupta et al, 2015). To determine whether they act similarly in maize seedlings, small RNAs were extracted and isolated at the same time points as in the RNAseq analysis.…”
Section: Regulation Of Micrornas During Mid Phasementioning
confidence: 99%